Design and fabrication of a robotic arm for material handling / P Nageswara Rao ... [et al.] - Rao, P Nageswara; Ahmad, Anuar; Omar, Abdul Rahman; Ayub, Muhammad Azmi (Institute of Research, Development and Commercialisation (IRDC), 2005)
The commercial robots are expensive for use in the educational institutions. The operation of them will not leave room for experimentation, which is necessary in an educational institution. Further a large number of components that can be used for building a robot are readily available in the market. Hence this project has been taken up to allow us to build a working robot using as many of the off the shelf components to provide the necessary flexibility. This would make it a low cost robot with enough flexibility for the students to experiment the various functions of the robot.